2019
DOI: 10.1123/wspaj.2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

The Alberta Women in Sport Leadership Project: A Social Learning Intervention for Gender Equity and Leadership Development

Abstract: This best practice paper describes a Canadian intervention to address the lack of women in sport coaching and leadership roles. While the number of female athletes has increased over the last decades, the opposite is true of female head coaches, both nationally and internationally. The issues influencing this trend are mostly institutional and societal. There is a lack of support systems in place for females attempting to become involved (recruitment) and maintain their involvement (retention) in coaching. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Multiple papers in this special issue outlined and evaluated programs targeted to develop women coaches. Allen and Reid (2019) and Culver et al (2019) specified multifaceted programs, best practices, and lessons learned for developing women coaches in Scotland and Canada, respectively. Both papers add practical and applied knowledge of supports at the individual and interpersonal levels of the EIM model, that can be adapted to other contexts to help develop and retain women coaches and improve equitable representation of women leaders in sport.…”
Section: Locating the Wspaj Special Issue Papers Within The Eimmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple papers in this special issue outlined and evaluated programs targeted to develop women coaches. Allen and Reid (2019) and Culver et al (2019) specified multifaceted programs, best practices, and lessons learned for developing women coaches in Scotland and Canada, respectively. Both papers add practical and applied knowledge of supports at the individual and interpersonal levels of the EIM model, that can be adapted to other contexts to help develop and retain women coaches and improve equitable representation of women leaders in sport.…”
Section: Locating the Wspaj Special Issue Papers Within The Eimmentioning
confidence: 99%
“…By explicitly demonstrating that women coaches have value, and, in turn, those who support them have value, the organizational climate for women coaches will change. Culver et al (2019) provides another programming, or educational, pathway to change. The coaches in her article identified that they valued more self-directed education as opposed to being the passive recipients of coaching instruction.…”
Section: Gaps Remain In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Bronfenbrenner's (1977Bronfenbrenner's ( , 1979 Ecological Systems Theory (EST) accounts for "how" systems have enabled the learning in this community, whereas Wenger, Trayner, and de Laat's (2011) Value Creation Framework (VCF) reveals "what" value has been created for these women in this social learning space. The EST has previously been used to identify barriers for women in leadership across sport systems (Burton, 2015;LaVoi & Dutove, 2012) and the VCF has been used as a tool to assess value, particularly in the context of social learning spaces for women coaches in sport (Bertram, Culver, & Gilbert, 2017;Culver et al, 2019). Below are descriptions of ecological systems and value creation cycles along with examples from the WiSL.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For the purpose of this practice paper, we focus on one of these 12 sport organizations to take a closer look at their initiative titled Women in Sport Leadership (WiSL). Readers are referred to Culver, Kraft, Din, and Cayer (2019) for more information on the larger AWiSL program. In this practice paper, we describe the systems which supported this initiative and the value of using, in this practice case, a women-only training program (WOTP; the model used for the WiSL) from the perspectives of two women in the program and two lead facilitators.…”
mentioning
confidence: 99%